Towards an open world economy - Corbet, Hugh.; Trade Policy Research Centre (London : Macmillan for the Trade Policy Research Centre, 1972)
This book is a report from the trade policy research centre by an advisory group chaired by McFadzean of Kelvinside
Includes bibliographical p. 171-181.
ijb 17/01/2019
Loans
Keywords: Commercial policy; International economic relations